PENGUATAN KARAKTER NASIONALIS DAN MANDIRI PADA SISWA SEKOLAH DASAR: STRATEGI DAN IMPLEMENTASI - Nurul Hidayah; Silfa Ayu Prastika; Maulida Nur Khasanah; Desi Fitria Sari; Ali Ahmad; Indik Syahrabanu; Ika Yatri; Muhammad Azhar Nawawi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Character education in elementary schools plays a crucial role in shaping a young generation imbued with national spirit and independence. However, its implementation is fraught with challenges. This study aims to underscore the significance of integrating nationalism and independence values into education to address the increasingly concerning moral and character issues in Indonesia. Employing a descriptive qualitative approach through previous literature case studies, the research reveals that fostering nationalist character involves teaching Pancasila values, conducting flag ceremonies, and engaging in Scout activities. On the other hand, promoting independent character is achieved through contextual learning, educational visits, and promoting proficient use of the Indonesian language. Challenges include insufficient teacher comprehension, inadequate support for facilities and infrastructure, and the pervasive influence of globalization. Proposed solutions encompass integrating character education into the curriculum, instilling positive values, bolstering school culture, and enhancing teacher training. In conclusion, there is a pressing need for improved collaboration among schools, parents, and the community to nurture nationalist and independent character traits.